TOT3–AHA1 module: its role in fine-tuning stomatal responses - Gong, Lei; Alabdallah, Nadiyah M.; Altihani, Faizah Amer; AL-Balawi, Siham M.; Anazi, Hanan Khalaf; Alharbi, Basmah M.; Hasan, Md. Mahadi (Frontiers in Plant Science, 2025)
Stomatal pores, controlled by surrounding guard cells, play a crucial role in balancing carbon dioxide (CO2) uptake and water loss in plants. Recent studies in Arabidopsis thaliana have identified the TARGET OF TEMPERATURE 3 (TOT3)–plasma membrane (PM) H+-ATPase (AHA1) module as a key player in stomatal movement, though its exact role in vascular plants is not yet fully understood. TOT3, a transcriptional regulator, influences the activity of AHA1, which regulates ion fluxes essential for stomatal opening. Under high-temperature conditions, TOT3 promotes stomatal opening, while OST1, a key regulator of drought-induced stomatal closure, inactivates TOT3 through phosphorylation. This phosphorylation serves as a molecular switch, adjusting stomatal aperture in response to heat and drought stress. Moreover, light may also impact stomatal movement via the TOT3–AHA1 interaction. This review explores the molecular mechanisms underlying the TOT3–AHA1 module, its integration with abscisic acid (ABA) signaling, and its role in plant adaptation to environmental stresses. Understanding this pathway could contribute to developing crops with enhanced water-use efficiency and resilience to abiotic stress.